Recrystallization in two-phase alloys - Baker, I; Ian Baker (1982)
﻿ This study is concerned with the effect of particles, which are too small to produce Particle Stimulated Nucleation, on recrystallization. A single crystal model system of internally oxidised copper-aluminium was deformed by rolling. The deformed and annealed structures were investigated both electron-microscopically and optically. Measurements of the stored energy of deformation were combined with measurements of the recrystallization kinetics by the use of anisothermal differential scanning calorimetry. The effect of particles on the mechanical properties of metals and the microstructural inhomogeneities produced during deformation in the single phase are reviewed. The literature concerning recrystallization is surveyed with emphasis on the possible sites for nucleation and the effects of a second phase. Comparison of the deformed structure of copper-alumina and copper revealed that cells form at lower strains in the particle-containing material. These cells are smaller than those found in copper and show alignment with {111} planes. Dynamic recovery at higher strains leads to the formation of a banded structure from these cells. Microbands were found at all strains, they increased in frequency and decreased in width as the strain increased. Misorientation measurements using STEM microdiffraction could find no evidence of a slip homogenizing effect due to the particles, in fact larger misorientations were found across cell boundaries in particle-containing material. Addition of particles raised the stored energy and this increase was greater at higher strains. A comparison of the recrystallization kinetics of particle-hardened and single phase material found complex behaviour in the former. Increasing the strain could lead to a change from complete suppression, to retardation, to acceleration of recrystallization in two-phase alloys. A model based on the properties of microbands and particle pinning is presented to account for these effects.